Teaching competencies for preparatory class teachers - Guersas, Hocine (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aimed to identify the most important personal and professional competencies required for teachers of preparatory education departments at the primary school level, by reviewing some previous foreign and local studies that dealt with these competencies at the preparatory education stage, considering it a preparatory stage for children for formal education. The results obtained led to the existence of basic competencies such as specialized academic training, a deep understanding of child development, and training in first aid and safety, and secondary competencies related to communication with students, communication with parents, and active listening, classroom management competencies such as behavior management and time management strategies, pedagogical and educational competencies such as lesson planning and curriculum development, differentiated instruction, and the use of educational technology, emotional and social competencies such as the skill of developing emotional intelligence and the skill of modeling emotional awareness, creative and artistic competencies that include the skill of integrating arts and crafts, vocal and motor activity competencies that include the strategy of group songs, the strategy of movement games, storytelling, and dramatic plays, physical and bodily competencies that include promoting physical activity and motor skills, organizing play, and ensuring health and healthy nutrition in the preschool environment, in addition to some personal competencies such as love for the teaching profession, love for children, fun and activity, love of innovation and discovery, emotional balance and emotional maturity, and respect for the ethics of the teaching profession.